Zulässigkeit und Grenzen der Projektbefristung - Schaich, Marie-Katrin (Abhandlungen zum deutschen und internationalen Arbeits- und Sozialrecht (ADIA), 2023)
»The Admissibility of Fixed-term Contracts only for the Duration of a Project«: Particularly in the public sector, the conclusion and renewal of fixed-term employment contracts is often made dependent on third parties providing the employer with funding for the implementation of a specific project. The author examines the admissibility of those fixed-term contracts only for the duration of a project. She concludes that the jurisdiction of the German Federal Labour Court on these cases is, in particular, incompatible with European Union law.